1999
DOI: 10.1046/j.1365-3059.1999.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Erwinia pyrifoliae, an Erwinia species different from Erwinia amylovora, causes a necrotic disease of Asian pear trees

Abstract: Bacteria from necrotic branches of Asian pear trees (Pyrus pyrifolia) in Korea were consistently isolated as white colonies on nutrient agar and formed mucoid, slightly yellow colonies on a minimal medium with copper sulphate. Isolates with this colony morphology were studied in a series of microbiological, molecular and pathological tests. Most isolates allowed the verification of Koch's postulate on P. pyrifolia seedlings and on slices from immature pear (Pyrus communis) fruits and were also positive in hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 15 publications
1
52
0
1
Order By: Relevance
“…Recently, a bacterial pathogen, Erwinia pyrifoliae, was characterized as a novel Erwinia species that also causes necrotic symptoms on Asian pears Rhim et al, 1999). The Asian pear pathogen was first detected in orchards near Chuncheon, South Korea, and has not been reported to occur in other countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a bacterial pathogen, Erwinia pyrifoliae, was characterized as a novel Erwinia species that also causes necrotic symptoms on Asian pears Rhim et al, 1999). The Asian pear pathogen was first detected in orchards near Chuncheon, South Korea, and has not been reported to occur in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Isolates from Japanese orchards described by Beer et al (1996) and Kim et al (1996) were characterized for molecular properties and were found to differ from Erwinia amylovora, but to be related to Erwinia pyrifoliae, the novel species causing Asian pear blight Rhim et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A bacterial disease similar to fire blight was observed on Nashi pear trees (Pyrus pyrifolia) in South Korea, caused by the novel species Erwinia pyrifoliae (16). The pathogen was consistently isolated from orchards in the area of Chuncheon from 1995 to 1998 and identified on semiselective agar plates and by PCR (15,16).…”
mentioning
confidence: 99%
“…The pathogen was consistently isolated from orchards in the area of Chuncheon from 1995 to 1998 and identified on semiselective agar plates and by PCR (15,16). E. pyrifoliae is restricted mainly to pear and is highly related to pear-pathogenic Erwinia strains from Japan (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation